2011
DOI: 10.2190/pm.42.1.b
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Religious Attendance and Blood Pressure: The Hunt Study, Norway

Abstract: In a large population-based survey in Norway, RA was associated with lower DBP and SBP after adjusting for relevant variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 19 publications
1
24
0
4
Order By: Relevance
“…Using a cold pressor stress response test in healthy subjects, blood pressure, pulse and serum cortisol were less increased in religious subjects than in non-religious subjects when exposed to acute painful stress [21]. Further support of stress alleviation includes the association between RA and low blood pressure [22] and between spirituality and lower urinary cortisol excretion in chronic pain patients [23]. An interesting explanation of the association between migraine and RA may be the possibility that spirituality is a way to reduce the allostatic load (biological consequences of chronic exposure to repeated or chronic stress responses) that has been suspected in migraine and other pain conditions [24].…”
Section: Discussionmentioning
confidence: 99%
“…Using a cold pressor stress response test in healthy subjects, blood pressure, pulse and serum cortisol were less increased in religious subjects than in non-religious subjects when exposed to acute painful stress [21]. Further support of stress alleviation includes the association between RA and low blood pressure [22] and between spirituality and lower urinary cortisol excretion in chronic pain patients [23]. An interesting explanation of the association between migraine and RA may be the possibility that spirituality is a way to reduce the allostatic load (biological consequences of chronic exposure to repeated or chronic stress responses) that has been suspected in migraine and other pain conditions [24].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also found that meditation reduces cortisol levels, high levels of which can have myriad negative effects on health, such as immunosuppression, insulin resistance, cardiovascular disease, and neuron atrophy (Koenig et al, ; Carlson et al, ; Tang et al, ). Frequent or regular attendance at religious services is associated with reduced blood pressure (Sørensen et al, ), lower prevalence of coronary heart disease (Banerjee et al, ), lower risk of stroke (Obisesan et al, ), and lower overall mortality risks (Gillum et al, ). The disease contexts of medieval populations and the living populations in which most studies of health and religion are conducted are certainly quite different, with higher infectious disease mortality in the former.…”
Section: Discussionmentioning
confidence: 99%
“…The literature review focused on the relationship between religious attendance, prayer, meditation and associated blood‐pressure recordings. Several studies found an association between frequency of religious attendance (once/week) and lower blood pressure when compared with people who attended religious services infrequently (< once/week) (Gillum & Ingram, ; Sørensen et al ., ; Bell et al ., ; Koenig et al ., ). Frequency of prayer has also been found to be related to lower blood pressure (Bernardi et al ., ; Belding et al ., ).…”
Section: Introductionmentioning
confidence: 97%